Atividade física e sua associação com qualidade de vida em pacientes com osteoartrite - Figueiredo Neto, Esmeraldino Monteiro de; Queluz, Thais Helena Abrahão Thomaz [UNESP]; Freire, Beatriz Funayama Alvarenga [UNESP] (Elsevier Editora Ltda, 2011)
OBJETIVO: Avaliar a qualidade de vida e sua associação com a atividade física nos diferentes contextos da vida diária de pacientes com osteoartrite (OA) encaminhados pelas unidades básicas de saúde para um serviço universitário. MÉTODOS: Estudo transversal, série de casos, em que a atividade física foi avaliada pelo International Physical Activity Questionnaire (IPAQ) e a qualidade de vida foi avaliada pelos questionários Medical Outcomes Study 36 Short-Form Health Survey (SF-36), Western Ontario and McMaster Universities Index (WOMAC) e Australian/Canadian Osteoarthritis Hand Index (AUSCAN). Para verificação da intensidade da dor, utilizou-se também a Escala Visual Analógica (EVA). RESULTADOS: Foram incluídos 100 pacientes (92 mulheres e oito homens), com média de idade de 59,9 ± 9,4 anos. As articulações mais comprometidas foram joelhos e mãos. Dez pacientes tinham comprometimento de uma única articulação, 69 de duas, oito de três e 13 de quatro. O IPAQ demonstrou que 70 pacientes eram ativos ou muito ativos e 30 eram insuficientemente ativos ou sedentários. A atividade física associou-se positivamente aos domínios do SF-36, que avaliam a saúde física (capacidade funcional, aspectos físicos, dor, estado geral da saúde). Houve associação entre atividade física e qualidade de vida quando avaliada pelo WOMAC, e quanto mais intensa a dor, pior a qualidade de vida. CONCLUSÃO: Nessa população, a maioria dos pacientes apresenta piora dos aspectos físicos da qualidade de vida, mas mantém as atividades físicas cotidianas.

OBJECTIVE: To evaluate the quality of life and its association with daily physical activity in different contexts of life in osteoarthritis patients referred from Basic Health Care Units to a university-affiliated service. METHODS: This is a crosssectional, case series study in which physical activity was evaluated by the International Physical Activity Questionnaire (IPAQ), and quality of life was assessed by the Medical Outcomes Study 36 Short-Form Health Survey (SF-36), Western Ontario and McMaster Universities Index (WOMAC), and Australian/Canadian Osteoarthritis Hand Index (AUSCAN). To evaluate pain intensity, a Visual Analogue Scale (VAS) was also used. RESULTS: One hundred patients (92 women and eight men; mean age 59.9 ± 9.4 years) were included. The most affected joints were the knees and hands. Ten patients had only a single joint affected, 69 patients had two, eight patients had three, and 13 patients had four joints affected. The IPAQ showed that 70 patients were active or very active, while 30 were insufficiently active or sedentary. Physical activity was positively associated with the SF-36 domains that assess physical health (physical functioning, physical role, pain, general health perceptions). There was an association between physical activity and quality of life assessed by WOMAC, and the more severe the pain, the worse the quality of life. CONCLUSION: In most patients in this population, the physical aspects of the quality of life are worse, but they maintain their daily physical activities.
Physical activity and its association with quality of life in patients with osteoarthritis
Keywords: osteoartrite; atividade motora; qualidade de vida; osteoarthritis; motor activity; quality of life